Evaluation of Onion Genotypes for Growth and Bulb Yield in Mid Hill of Nepal - Gautam, Ishwori Prasad; Pradhan, Navin Gopal; Luitel, Binod Prasad; Subedi, Sujan (Journal of Nepal Agricultural Research Council, 2019)
Experiments were conducted at Horticulture Research Division (HRD), Khumaltar, Lalitpur; and Horticulture Research Station (HRS), Kimugaun, Dailekh in 2017/18 to evaluate the high yielding open pollinated genotypes of onion in mid hills of both locations. Five onion genotypes namely AVON-1016, AVON-1027, AVON-1028, AVON-1052, AVON-1074 and AVON-1103 received from Asian Vegetable Research and Development Centre were evaluated with local check variety and recommended variety Red Creole in both locations in randomized complete block design with 4 replications. The main objective of the experiment is to findout the high yielding open pollinated onion genotypes for mid hill condition.The pooled analysis of data over locations showed significant differences on plant height, neck diameter, bulb diameter, weight of bulbs and adjusted bulb yield per hectare. Introduced genotypes AVON 1027 (38.83 t/ha), AVON 1052 (31.97 t/ha) and AVON 1028 (31.48 t/ha) produced significantly higher yield than recommended and commercially cultivated check variety Red Creole (27.04 t/ha). Therefore the genotype AVON 1027 can be selected as the best genotype for growing in mid hills of Nepal